1996
DOI: 10.1071/wr9960099
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Wild and Hand-reared Ringtail Possums (Pseudocheirus peregrinus) in Bushland near Sydney

Abstract: Radio-tracking studies of ringtail possums (Pseudocheirus peregrinus) were carried out in Ku-ring-gai Chase National Park at its border with suburban Sydney. Hand-reared and relocated ringtail possums released into the study site survived an average of 101 days and wild ringtail possums resident in the study area survived an average 182 days. Of the 118 individuals whose fates were determined, all but eight were killed by predators, 52% by foxes and 29% by cats. Within the study area both introduced and wild r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 6 publications
(9 reference statements)
2
27
0
Order By: Relevance
“…This explanation is also plausible here. However, the consistent inclusion of R. fuscipes and A. stuartii in the diet of the fox at all times of the year in the present study area (Augee et al 1996;Sutherland 1998) suggests that some selective advantage should nonetheless accrue to individuals that can discriminate and avoid cues to fox presence.…”
Section: Discussionmentioning
confidence: 61%
“…This explanation is also plausible here. However, the consistent inclusion of R. fuscipes and A. stuartii in the diet of the fox at all times of the year in the present study area (Augee et al 1996;Sutherland 1998) suggests that some selective advantage should nonetheless accrue to individuals that can discriminate and avoid cues to fox presence.…”
Section: Discussionmentioning
confidence: 61%
“…The finding that hand-reared animals do not survive well when returned to the wild is not new, nor restricted to flying-foxes. Augee et al (1996) reported poor survival of 'rehabilitated' ringtail possums; Mathews et al (2005) issued a general caution that captive animals are often unsuitable for re-establishing wild populations and Kelly et al (2008) found that hand-reared pipistrelle bats experienced poor survival post-release. The results from the present study suggest that the direct conservation benefit of hand-rearing flying-foxes is minimal, although it seems highly likely that there are significant indirect benefits through improving the generally poor public image of bats.…”
Section: Life Expectancy Of Hand-reared P Poliocephalusmentioning
confidence: 97%
“…Road-kill is a significant contributor to macropodid mortality, particularly so for wallaby species (Taylor and Goldingay, 2003;Ramp et al, 2006). From dietary studies it is know that at some locations, in particular in coastal New South Wales, swamp wallabies are the preferred wildlife dietary item of dingoes (Robertshaw and Harden, 1986), feral and domestic dogs (Lunney et al, 1990;Meek and Triggs, 1998), as well as a significant component of fox diets (Augee et al, 1996). The presence and predation of swamp wallabies by dogs and foxes has been confirmed at Muogamarra Nature Reserve through foot print surveys, collection of fecal pellets and photography (Ben-Ami, 2005).…”
Section: Study Site and Speciesmentioning
confidence: 99%